A study on the physical aging characteristics of the older people over 70 years old in China - Shen, Jin-Bo; Ma, Yuan-Yuan; Niu, Qian (Frontiers in Public Health, 2024)
Aim In China, with the increase of life expectancy and the decrease of fertility rate, the aging problem has become increasingly prominent, and the physical problems of the older people over 70 years are the key and difficult problems. Method Based on the interactive logic between the aging problem and the older people health, in the study, a questionnaire survey and a nationwide physical fitness test were carried out on the older people over 70, to divide into different age groups (70–74 years old, 75–79 years old, 80–84 years old, 85 years old and older) and different genders. There were 8,400 valid samples, and 1,050 persons in each group. One-way ANOVA was used to compare the differences among groups of different ages, and a broken line chart was drawn to discuss the aging characteristics of various physical indexes of the older people over 70 in China. Result (1) Body morphology: male waist circumference, male waist-to-height ratio and female BMI showed a gradual downward trend with the increase of age; (2) Physiological function: male and female vital capacity showed a decreasing trend with the increase of age, while female pulse pressure showed a gradual upward trend. (3) Physical quality: the indicators of male and female muscle strength, flexibility quality, aerobic endurance and balance showed a downward trend with the increase of age. Conclusion Vital capacity, flexibility quality, muscle strength, aerobic endurance, balance ability and so on, decreased significantly with the growth of age. 80 years old is the inflection point of the rapid decline of various indicators. Blood pressure, silent pulse, BMI, waist-to-hip ratio, waist-to-height ratio and other indicators did not change regularly with age. Indicators such as blood pressure, BMI, waist-to-hip ratio and waist-to-height ratio were in the high-risk range of metabolic diseases and cardiovascular and cerebrovascular diseases. The study conducted physical fitness test on the older people over 70 years old in 7 geographical regions of China, which is the first nationwide physical fitness test for the older people, which is an extension and expansion of the national physical fitness monitoring system, and also shows that the test indicators involved in the “Health fitness scale” are simple and feasible. And the study added a series of test data over 70 years old, which is the basis for scientific and reasonable formulation of physical fitness evaluation standards for the older people, and is of great significance for improving the national physical fitness database and grasping the dynamic changes of national physical health status, and providing data support for scientific guidance of physical exercise for the older people.